Description of one new species of the genus Gymnogryllus (Orthoptera, Gryllidae, Gryllinae) from Cameroon with a key for African species - Nyobe, Philene Corinne Aude Um; Ngoute, Charly Oumarou; Richard, Nzoko Fiemapong Armand; Robillard, Tony; Ma, Libin; Kekeunou, Sevilor (Zootaxa, 2023)
During a Gryllidae survey in the Southern Cameroonian Plateau, one new species of the genus Gymnogryllus (Orthoptera, Gryllidae, Gryllinae) was discovered and described, namely Gymnogryllus bilongi Um Nyobe & Kekeunou sp. nov. This finding extends the number of species known of this genus in Cameroon at two and proposes a key for African species.